2011
DOI: 10.1186/1472-6963-11-76
|View full text |Cite
|
Sign up to set email alerts
|

Day care for dementia patients from a family caregiver's point of view: A questionnaire study on expected quality and predictors of utilisation - Part II

Abstract: BackgroundThe investigation of the predictive variables for utilisation of day care and the views of family caregivers of dementia patients about quality of day care are the goals of this work.MethodsThe cross-sectional study was carried out as an anonymous written survey of family caregivers of dementia patients in Germany. Participants were 404 family caregivers of dementia patients, of these 128 were users of day care, 269 were non-users and 7 gave no details about utilisation. Qualitative and quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 29 publications
3
33
1
9
Order By: Relevance
“…Short and fixed opening hours and the lack of service during public holidays and vacations give relatives limited opportunities for an active social life, especially in the evenings. The need for flexible opening hours, as expressed by the family caregivers, confirms previous research that showed that flexible opening hours and programmes are important for the DCCs to provide respite [31,36,48]. Social stress is one of the factors affecting the burden on the family caregiver [10,12].…”
Section: Limited Opening Hours -Consequences For the Caregiver's Socisupporting
confidence: 79%
See 1 more Smart Citation
“…Short and fixed opening hours and the lack of service during public holidays and vacations give relatives limited opportunities for an active social life, especially in the evenings. The need for flexible opening hours, as expressed by the family caregivers, confirms previous research that showed that flexible opening hours and programmes are important for the DCCs to provide respite [31,36,48]. Social stress is one of the factors affecting the burden on the family caregiver [10,12].…”
Section: Limited Opening Hours -Consequences For the Caregiver's Socisupporting
confidence: 79%
“…Some studies indicate decreased symptoms of depression in caregivers when the person with dementia attends a DCC [9,28], but other studies find no significant effect on wellbeing [25,27]. 4) DCCs increase motivation for care and postponement of the need for residential care as they offer information and support regarding dementia-related topics, with the intention to reduce care-related stress [5,8,11,25,28,31,32]. Support for family caregivers aims to develop knowledge and skills in dementia care and prevent the risk of early institutional placement [11,33].…”
Section: Introductionmentioning
confidence: 99%
“…Benefi ts of day programmes include stress reduction for family caregivers (Grinberg et al, 2008;Zarit et al, 2011) as well as helping dementia patients have more structure and stimulation, which in turn are important factors in caregivers ' choice to have their spouse attend a day programme (Donath et al, 2011). Studies have suggested that AD patients respond to recreational activities such as gardening, music and exercise with benefi ts to behaviour and quality of life (Cooke et al, 2010 ;Lee & Kim, 2008;Venturelli et al, 2011).…”
Section: Specialized Day Programme For People With Ftdmentioning
confidence: 99%
“…Clients and their family carers have positively appraised the knowledge, skill and ability of day centre staff to address complex needs, citing these among the main reasons for using day care services (Donath, Winkler, Graessel, & Luttenberger, ; Lecovich & Biderman, ). There is evidence to suggest that family carers have much to gain from the attendance of their loved one at day centres.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that family carers have much to gain from the attendance of their loved one at day centres. The respite from caring responsibilities for even a few hours each week can impact positively on the resilience and coping of carers (Donath et al., ). Despite the potential benefits of day care, some older adults refuse to attend.…”
Section: Introductionmentioning
confidence: 99%